MODELING APPROACH TO URBAN VULNERABILITY TO FLOODING IN THE METROPOLITAN AREA OF ANNABA - Salah Sid,; Boureboune Lamia, (International Journal of Innovative Technologies in Social Science, 2024)
Historically, natural hazards have been a constant presence in Mediterranean regions. Earthquakes, eruptions, and floods frequently impact various territories, underscoring this reality. Consequently, governments have prioritized the establishment of prevention, management, and alert systems, making fundamental applied research essential for the ongoing development of these nations. Algeria has experienced numerous natural disasters in the past, particularly those associated with major earthquakes, such as the El Asnam earthquake on October 10, 1980, the Boumerdes earthquake on May 21, 2003, the Bab El Oued floods on November 10, 2001, and more recently, the Ghardaia floods on October 1, 2008.The general living conditions in Algeria, especially in urban areas, are characterized by insufficient management of various issues, largely due to rapid growth. This has at times led to unregulated and uncontrolled urban expansion, with developments on riverbeds, unstable slopes, and other high-risk areas. Such urbanization fails to consider the persistent presence of natural hazards, which are further intensified by climate change.Our objective is to identify the primary causes of natural risks and disasters in urban areas. This study includes an illustrative case in the intermunicipal area of Annaba, located in northeastern Algeria, where flood risk remains significant. The study aims to assess the impact of climate change and the support provided for crisis prevention and management within a sustainable framework.